IMPACT OF ILLEGAL OIL MINING: WHAT SHOULD GOVERNMENT DO? - Zailani Surya Marpaung; Tuty Khairunnisa; Slamet Widodo; Imelda Imelda (Jurnal Kebijakan Publik, 2023)
The rampant practice of illegal oil well mining by the community in Musi Banyuasin district has caused various impacts, namely environmental impacts in the form of pollution, the impact of causing fatalities due to oil well exploration accidents, the impact of social conflict, and the impact of vulnerability and order. Due to the current unclear policy from the government to regulate the Management of Community Oil Wells, comprehensive governance is needed which includes Institutional Governance and Mapping of Oil Well Clusters, Governance of Safety Aspects, Occupational Health and Environmental Management, Governance of Strengthening the Capacity of Community Groups, Governance of the Management and Production of Community Oil Wells from upstream to downstream. To produce administrative benefits in the form of absorption of labor, calm for the community in carrying out their activities, reduced crime rates and crime rates, and profits obtained by local governments from tax revenues which can ultimately be used to realize community welfare programs.